Immunophenotyping for diagnosis and prognosis in MDS: Ready for general application?. Issue 1 (March 2015) - Cremers, Eline M.P.; Alhan, Canan; Westers, Theresia M.; Ossenkoppele, Gert J.; van de Loosdrecht, Arjan A.
<x xml:space="preserve">Abstract</x> Myelodysplastic syndromes is a heterogeneous group of bone marrow diseases ranging from low risk to high risk subtypes that may rapidly evolve to acute myeloid leukemia. Flow cytometry (FCM) is added as a recommended tool for diagnostic purposes in MDS. In recent studies FCM has also shown applicable to predict prognosis and treatment response. This review summarizes current data about the diagnostic, prognostic and therapeutic value of FCM in MDS. The high sensitivity of FCM in the detection of dysplasia in myelo-/monocytic and erythroid cell lineages makes it a valuable tool to distinguish possible clonal causes of cytopenia(s) from non-clonal causes, and to detect multi-lineage dysplasia in addition to cytomorphology. The utility of FCM in prediction of treatment response is promising. Therefore, FCM is an essential tool in standard diagnostic strategies in case of suspected MDS, and ready for general application.